Matrices of LCAO-Hamiltonian in special points - Don, N.; Ivchenko, V.; Remnyova, V. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2008)
Semiconductors of AII3BV2 group have the structures very near to cubic close packed lattices. Their cation’s vacancies might be either in positional disorder or vice versa. This detail directly affects on so-called “structural factors” of the matrix elements of the Hamiltonian. The matrix elements change itself just depending on supposition about the degree of vacancies ordering. These investigations show that the part of energy levels is straightly depending on the degree of vacancies ordering, whereas other part of them is independent.